Penerapan Pendidikan Karakter Dalam Pendidikan Islam Modern: Studi Kasus di Sekolah-Sekolah Islam - Dian Ika Safitriana; Nur Khasanah (An-Nuha, 2024)
Character building should be systematic and continuous, focusing on moral knowledge (moral knowing), emotional empathy (moral feeling), and virtuous behavior (moral action). Emphasizing habit formation, character education nurtures values that help students become responsible individuals in daily life. This research uses a qualitative approach with library research to gather data from books, journals, and other relevant sources. The main references are texts on character education with a foundation in religious values. Character education not only addresses academic skills but also instills moral values, equipping students to handle conflicts, make wise decisions, and build positive relationships. The evaluation of Islamic religious education measures students' progress in knowledge, skills, and attitudes, helping assess their mastery of the provided lessons.